INTERACTIVE SMARTBOARD: Apakah dapat meningkatkan kemampuan berpikir kritis siswa? - Ni Nengah Widyartini; Edy Herianto; Edy Kurniawansyah; Muh. Zubair (Jurnal Penelitian dan Pendidikan IPS, 2024)
This study aims to determine the effect of the application of interactive use of smartboards on students' critical thinking skills in order to realize the sustainable development goals (SDGs). This study uses a quantitative approach with a quasi-experimental type through a non-equivalent control group design. The population is class X which consists of 15 classes and the research sample, namely class X12 as an experimental class and X6 as a control class. The data collection technique used consists of tests and observations. The results of the prerequisite test showed that the data was distributed normally and homogeneously, so to test the hypothesis use ujit. The results were > ttable (8,502 >2,036), meaning that the use of interactive smart boards had an impact on the acquisition of students' thinking skills in order to realize the SDGs.